How Online Privacy Literacy Supports Self-Data Protection and Self-Determination in the Age of Information - Philipp K. Masur (Media and Communication, 2020)
Current debates on online privacy are rooted in liberal theory. Accordingly, privacy is often regarded as a form of freedom from social, economic, and institutional influences. Such a negative perspective on privacy, however, focuses too much on how individuals can be protected or can protect themselves, instead of challenging the necessity of protection itself. In this article, I argue that increasing online privacy literacy not only empowers individuals to achieve (a necessarily limited) form of negative privacy, but has the potential to facilitate a privacy deliberation process in which individuals become agents of social change that could lead to conditions of positive privacy and informational self-determination. To this end, I propose a four-dimensional model of online privacy literacy that encompasses factual privacy knowledge, privacy-related reflection abilities, privacy and data protection skills, and critical privacy literacy. I then outline how this combination of knowledge, abilities, and skills 1) enables to individuals to protect themselves against some horizontal and vertical privacy intrusions and 2) motivates individuals to critically challenge the social structures and power relations that necessitate the need for protection in the first place. Understanding these processes, as well as critically engaging with the normative premises and implications of the predominant negative concepts of privacy, offers a more nuanced direction for future research on online privacy literacy and privacy in general.